Smart Strawberry Advisory System for Mobile Devices - Clyde W. Fraisse; Natalia A. Peres; José Henrique Debastiani Andreis (EDIS)
Like the web-based SAS, the SAS: Strawberry Advisory System mobile app monitors real-time and forecast weather conditions that increase the risk for Botrytis (gray mold) and anthracnose fruit rots, providing risk level information for each disease. The app provides easy access to the information growers need to make spraying decisions in the field, saving them time, helping improve disease control, and avoiding unnecessary fungicide applications. This 3-page fact sheet provides an overview of the SAS mobile app. Written by Clyde W. Fraisse, Natalia Peres, and José Henrique Andreis, and published by the UF Department of Agricultural and Biological Engineering, August 2015.